Intensive Math Instruction and Educational Attainment: Long-Run Impacts of Double-Dose Algebra - Kalena E. Cortes; Joshua Goodman; Takako Nomi (Institute for the Study of Labor (IZA), 2014)
We study an intensive math instruction policy that assigned low-skilled 9th graders to an algebra course that doubled instructional time, altered peer composition and emphasized problem solving skills. A regression discontinuity design shows substantial positive impacts of double-dose algebra on credits earned, test scores, high school graduation and college enrollment rates. Test score effects under-predict attainment effects, highlighting the importance of long-run evaluation of such a policy. Perhaps because the intervention focused on verbal exposition of mathematical concepts, the impact was largest for students with below average reading skills, emphasizing the need to target interventions toward appropriately skilled students.
Keywords: I20; I21; I24; J15; J24; 330; double-dose algebra; instructional time; peer effects; math curriculum; educational attainment; high school graduation; college enrollment